2011
DOI: 10.1177/1078155211419543
|View full text |Cite
|
Sign up to set email alerts
|

Verification of surface contamination of Japanese cyclophosphamide vials and an example of exposure by handling

Abstract: This study shows that the surface of Japanese CP vials was contaminated and that it was probable that healthcare workers were exposed to CP. CP absorption by the pharmacist was probably due to dermal uptake while dispensing. Washing the vial is considered effective to avoid CP exposure. Manufacturers should be more proactive to prevent contamination and healthcare workers should comply with exposure prevention rules. Cytotoxic drugs should be included in institution monitoring lists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In contrast, some other studies have found traces of hazardous drugs in the urine of healthcare workers. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Some of these studies have reported high proportions of workers with such contamination. For example, Hon et al 26 determined the concentration of cyclophosphamide after 24-h urine collection by 103 healthcare workers (201 samples) in six British Columbia hospitals from 2010 to 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some other studies have found traces of hazardous drugs in the urine of healthcare workers. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Some of these studies have reported high proportions of workers with such contamination. For example, Hon et al 26 determined the concentration of cyclophosphamide after 24-h urine collection by 103 healthcare workers (201 samples) in six British Columbia hospitals from 2010 to 2011.…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5) Drug residues are still found on various surfaces in and around the drug preparation area of (hospital) pharmacies and oncology wards, even on assumedly "clean" surfaces (6)(7)(8)(9)(10)(11)(12)(13)(14) and on the outside of vials. (15)(16)(17)(18)(19)(20)(21)(22)(23) Dermal contact followed by transdermal absorption is suggested to be the major route of incorporation in occupational settings. (24)(25)(26)(27) Apart from preventive measures, efficient cleaning strategies for decontamination of workstation surfaces must be consequently focused in terms of minimizing the risk of exposure to drug residues.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A total of 24 studies from 11 countries were included (Germany (n=3 studies), Australia (n=1), Belgium (n=3), Canada (n=6), the USA (n=2), France (n=2), Japan (n=3), the Netherlands (n=2), the UK (n=1), Sweden (n=2), Switzerland (n=1)) (online supplementary appendix 1). 4 5 10–31 Sampling was done by wiping the containers (n=20) or by immersion (n=3). Liquid chromatography tandem-mass spectrometry (n=15) and gas chromatography tandem-mass spectrometry (n=15) were mostly used to quantify the drugs.…”
Section: Resultsmentioning
confidence: 99%